2010
DOI: 10.1007/s10439-010-0104-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Intensity Pulsed Ultrasound on the Expression and Activity of Hyaluronan Synthase and Hyaluronidase in IL-1β-Stimulated Synovial Cells

Abstract: The purpose of this study is to examine effects of low-intensity pulsed ultrasound (LIPUS) on metabolism of hyaluronan (HA) in synovial membrane cells stimulated by IL-1β. Rabbit knee synovial membrane cell line, HIG-82, was cultured in medium with the presence or absence of 1 ng/mL IL-1β, and after 4 h the cell was exposed to LIPUS for 15 min. The mRNA levels of HA synthase (HAS) 2,3, hyaluronidase (HYAL) 2, and cyclooxygenase (COX)-2 were examined by real-time PCR analysis. Concentrations of HA and PGE₂ were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
3
17
0
Order By: Relevance
“…However, results from both the mRNA expression of the hyaluronidases shows that HYAL1 and HYAL2 are up-regulated by the treatment of IL-1β. This is in accordance with the study done by Nakamura et al, [25]. Findings from this data demonstrates that treatment with P. dasyphylla EA extract in response to human IL-1β has proven to be potential inhibiting the two principle hyaluronidases.…”
Section: Resultssupporting
confidence: 93%
“…However, results from both the mRNA expression of the hyaluronidases shows that HYAL1 and HYAL2 are up-regulated by the treatment of IL-1β. This is in accordance with the study done by Nakamura et al, [25]. Findings from this data demonstrates that treatment with P. dasyphylla EA extract in response to human IL-1β has proven to be potential inhibiting the two principle hyaluronidases.…”
Section: Resultssupporting
confidence: 93%
“…22 In addition, It was reported that LIPUS down-regulated the expression of Cox-2 mRNA in chondrocytes as well as synovial membrane cells (Y. Iwabuchi, Personal communication). In the present study, we showed that the expression of Cox-2 in the knee joints of MRL/lpr mice was markedly reduced by daily LIPUS exposure in vivo.…”
Section: Discussionmentioning
confidence: 96%
“…13 To the best of our knowledge, this is the first attempt to investigate the effects of LIPUS on the cell proliferation and growth of synovial membrane cells. The only available information about its effect on synovial membrane cells is from our previous study, 22 in which the effect of LIPUS on the IL-1b-stimulated metabolism of hyaluronic acid in synovial membrane cells was examined. We showed that gene and protein expression of Cox-2 as well as PGE 2 secretion were increased in the HIG-82 synovial membrane cell line following stimulation with IL-1b, and that the increased expression of Cox-2 was significantly inhibited by subsequent LIPUS exposure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations